Exploring the potential roles of biochars on land degradation mitigation - Berek, A K (Journal of Degraded and Mining Lands Management, 2014)
Land degradation was exacerbated and its management was challenged by population growth and global climate change. The impacts of land degradation on food security, ecosystem services and biodiversity become a more serious problem particularly in developing countries. Biochar, based on the current research findings, is capable to amend degraded lands. This paper reviewed relevant biocharproperties and identified the opportunities of its using for recovering deteriorated lands.Biochar was traditionally recognized as a good absorbent, energy source, and its ash was used by farmers to recover soil fertility. Recent findings revealed that application of biochar improved soil water retention, enhanced soil aggregation, decreased soil bulk density and increased soil infiltration. It also increased soil cation exchange capacity, soil pH, mineral nutrients, reduced nutrient leaching, support microbial population and activities, and suppressed the pest. The sorption capacity of biochar to soil and water pollutants such as Pb, Cu,Ni, Cr, Cd,dioxine, atrazine, and concurrently eliminatedthe environmental problems such as hypoxia, eutrophication, and algae bloom, have also been investigated. Investigation on its role to mitigate climate change revealed that biochar is capable in reducing greenhouse gasesemissions such as CO2, N2O, and CH4. All those beneficial effects of biochars were attributed to its high porosity, large surface area and surface charge, high carbon, ash and nutrient content, and its stability to be degraded. Thus, biochar could be potential for ameliorating degraded lands.